GIVING BOOSTER IMMUNIZATION IN TERMS OF MOTHER'S KNOWLEDGE LEVEL - Siska Delvia; M. Hasan Azhari (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
Booster immunization is a repeat or follow-up immunization given when toddlers are 18 months - 1.5 years old and given after getting basic immunization to maintain the level of immunity and extend the protection period of children who have received basic immunization. Booster immunization is given after basic immunization. Parents not understanding the importance of booster immunization is one of the many factors that influence the number of unimmunized children. This study aimed to determine the relationship between parents' knowledge and perceptions of booster immunization in under-fives at Tanjung Agung Health Center. This study used an analytic survey and quantitative design with a cross-sectional approach to identify the relationship between variables. All toddlers who came to the Tanjung Agung Baturaja Health Center were the subjects of this study. Primary, research data were collected through questionnaires distributed to respondent mothers during their visit to the Puskesmas Tanjung Agung Baturaja. The results showed that the education variable had a pvalue of 0.002 and the knowledge variable had a pvalue of 0.003. The results indicate that there is a significant correlation between knowledge and education with boster immunization in children at Puskesmas Tanjung Agung Baturaja.